Simulation of a non-Markovian evolution using coherence - Marrou Osores, Jean Paul (2019)
This thesis will be oriented in the study of open quantum systems. The transition of processes that go between the Markovian and non-Markovian regime will be studied. The diagnose of non-Markovianity will be made in terms of the variation of the coherence of the state. Accordingly, an optical setup will be implemented that allows us to manipulate certain degrees of freedom, like the polarization and the optical path. Theoretically, we have found that the coherence of the system is transferred to the environment and it decreases as we move a parameter that we will take as time. This situation has been confirmed in the experiment. Then, due to the second part of the setup, which produces a non-Markovian evolution by also changing one of its parameters, we have accomplished the goal of returning the information back into the system and to measure the non-Markovianity of the process.